The Role of the Bone Marrow Stromal Compartment in the Hematopoietic Response to Microbial Infections - Nombela-Arrieta, César; Isringhausen, Stephan (Frontiers in Immunology, 2017)
Continuous production of blood cells unfolds within a complex three-dimensional tissue scaffold established by highly organized stromal cell networks of mesenchymal, neural and vascular origin inside bone marrow cavities. Collectively, stromal cells have been shown to serve two principal roles; first as primary participants of bone remodeling and metabolism, second as master regulators of different stages of blood cell development and production. Indeed, ample evidence demonstrates that stromal cells can sense and integrate systemic signals to shape hematopoietic responses, and that these regulatory mechanisms are subverted in multiple pathologic conditions. Microbial infections are stressors that elicit potent inflammatory reactions and induce substantial alterations of hematopoietic output. Whether the cellular components of the BM stromal microenvironment are targeted by infections and participate in infection-induced hematopoiesis has not been investigated in sufficient detail to date. In this manuscript we provide a succinct updated overview of the different cell populations that are currently known to form BM stroma. We discuss experimental evidence demonstrating that different stromal components are actively damaged or functionally altered by pathogens and/or ensuing inflammatory signals, and review how these effects are known to contribute to the hematologic manifestations observed during infections.